The 2017 Plasma Roadmap: Low temperature plasma science and technology - Adamovich, I; Baalrud, S D; Bogaerts, A; Bruggeman, P J; Cappelli, M; Colombo, V; Czarnetzki, U; Ebert, U; Eden, J G; Favia, P; Graves, D B; Hamaguchi, S; et al. (Journal of physics. D, Applied physics, 2017)
Journal of Physics D: Applied Physics published the first Plasma Roadmap in 2012 consisting of the individual perspectives of 16 leading experts in the various sub-fields of low temperature plasma science and technology. The 2017 Plasma Roadmap is the first update of a planned series of periodic updates of the Plasma Roadmap. The continuously growing interdisciplinary nature of the low temperature plasma field and its equally broad range of applications are making it increasingly difficult to identify major challenges that encompass all of the many sub-fields and applications. This intellectual diversity is ultimately a strength of the field. The current state of the art for the 19 sub-fields addressed in this roadmap demonstrates the enviable track record of the low temperature plasma field in the development of plasmas as an enabling technology for a vast range of technologies that underpin our modern society. At the same time, the many important scientific and technological challenges shared in this roadmap show that the path forward is not only scientifically rich but has the potential to make wide and far reaching contributions to many societal challenges.